(3eSfO GdEeGe CMeO Hf MfHds - (3GdTjHGfj, GdeQhRj, GdHZOGOj, CHh YHO Gddg, CMeO Hf eMeO Hf MfHd, J (B241(3g`s ((3CMeO Hf eMeO GdfGHdSjs)
(3ChdgG (B:s
(3PGc GdQLd Ydi Njd aUMHJg eG CUMHg EdG Ydi HZVg YdjG bGd (B: (3aCUHfG SHjG bGd (B: (3acJH Edi QShd Gddg Udi Gddg Ydjg hSde GHYK EdjfG ef jNeSg bGd (B: (3aHYK EdjfG YdjG , haj GdSHj hUjaI gj ef CaVd GdSHj aNeS , hbSe aNQL QCSg (B((3h(B) (3QCSg eZWi s
(3BNQgG (B:s
(3Chd eSfO Ce GdeDefjf YGFTI QVj Gddg YfgG Cf QShd Gddg Udi Gddg Ydjg hSde fgi Yf bJd MjGJ GdHjhJ , EdG GdCHJQ , hPG GdWajJjf , aEfgeG jNJWaGf , Ch bGd (B: (3jWeSGf GdCHUGQ , hjWQMGf GdMHd ef HWhf GdfSGA , hef JQcgG adjS efG MOKfG YHO Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 203s
(3eYLe GdeDdajf (B1 / 261s
(3cTa GdXfhf (B2 / 1680s
(3JGQjN GdESdGe (B/ (3hajGJ (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs